The efficacy of Aeromonas hydrophila GPl-04 feed-based vaccine on African catfish (Clarias gariepinus) - Dini Siswani Mulia; TRI UTOMO; ALIM ISNANSETYO (Society for Indonesian Biodiversity, 2022)
Abstract. Mulia DS, Utomo T, Isnansetyo A. 2022. The efficacy of Aeromonas hydrophila GPl-04 feed-based vaccine on African catfish (Clarias gariepinus). Biodiversitas 23: 1505-1510. Aeromonas hydrophila is a pathogenic bacterium to African catfish (Clarias gariepinus). Vaccination is one of the strategic efforts to control this type of bacterial attack. The objective of this study was to determine the effectiveness of A. hydrophila GPl-04 feed-based vaccine for African catfish. This study used A. hydrophila GPl-04 strain isolate as vaccine material. Sample used was African catfish measuring 10-13 cm length, weighing 16-25 g, taken from aquaculture ponds in the Purbalingga area, Central Java, Indonesia. This study applied experiments under the completely randomized design (CRD) method with 5 treatments and 3 replications. The treatments consisted of P0: feed without vaccine (control); P1: feed with 10 mL/100 g dose of vaccine given for 10 days; P2: feed with 10 mL/100 g dose of vaccine given for 15 days; P3: feed with 15 mL/ 100 g dose of vaccine given for 10 days; and P4: feed with 15 mL/ 100 g dose of vaccine given for 15 days. The challenge test was carried out on week 3, by injecting 0.1 mL of A. hydrophila suspension at 105CFU/mL dose per fish. The main parameters included the fish antibody titer, survival rate (SR), relative percent survival (RPS), mean time to death (MTD), and growth rate. Supporting parameters included water quality such as water temperature, water pH, and dissolved O2 levels. The main parameter data were analyzed using analysis of variance (ANOVA) and Duncan multiple range test (DMRT) at 5% test level, and the supporting parameter was descriptively quantitative analyzed. The results showed A. hydrophila GPl-04 feed-based vaccine could increase antibody titer, SR, RPS, and MTD of African catfish (P<0.05). In addition, vaccination did not adversely affect the growth. The A. hydrophila GPl-04 feed-based vaccine was effective in protecting African catfish from A. hydrophila attack where 10 mL/100 g dose, given for 10 days (P1) was indicated as the most effective compared to other vaccination treatments.